Lymphatic Disorder Management in Pediatric Patients With Congenital Heart Disease in European Pediatric Cardiology Centers: Current Status, Disparities, and Future Considerations - Sanam Safi; Vibeke E. Hjortdal; Marc Gewillig; Owen Miller; Mohammad Ryan Abumehdi; Massimiliano Cantinotti; Heynric Grotenhuis; Francesca Raimondi; Almudena Ortiz Garrido; Arno Roest; Jan Sunnegårdh; Thomas Saleats; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Lymphatic disorders such as protein‐losing enteropathy, plastic bronchitis, and chylothorax are important complications of the Fontan circulation and ultimately result in an increased risk of early death. Several European centers are now performing lymphatic procedures. The aim of this study is to map the extent of these lymphatic disorders and treatments provided across European pediatric cardiology centers. Methods and Results A survey was circulated to 49 European pediatric cardiology centers consisting of 37 questions including a mix of binary, categorical, and continuous variables. Thirty‐one centers (63%) participated in the study, performing a median of 250 (interquartile range, 178 ‐ 313) cardiopulmonary bypass procedures per year. Chylothorax emerged as the most prevalent lymphatic disorder followed by protein‐losing enteropathy and plastic bronchitis. The most common diagnostic investigation method was noncontrast magnetic resonance lymphangiography (52%). Eleven centers (35%) conducted lymphatic interventions with a median of 3 (interquartile range, 1 ‐ 4) procedures per year and 12 (interquartile range, 5 ‐ 15) interventions in total per center. Conclusions This study confirms the rarity of and variation in treatment approaches for lymphatic disorders across Europe. With at least 11 centers offering lymphatic interventions, the adoption of these procedures is on the rise in Europe. To improve the quality of care and treatment outcomes for these complex patients, it is crucial to consider evidence‐based lymphatic diagnostics, interventional lymphatic procedures, and the centralization of services in Europe.